2003
DOI: 10.1111/j.1745-4573.2003.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organic Acid Marination on Tenderness, Cooking Loss and Bound Water Content of Beef

Abstract: Longissimus muscle obtained from beef carcasses was used in this research. Initially, 0.596, 1.0% and 1.5% lactic and citric acid solutions were prepared. Meat was marinated in these solutions (1:4 w/v) in polyethylene bags at 4C for 72h. Bound water, pH, weight gain, cooking loss and Warner Bratzler shear (WBS) were evaluated. Differential Scanning Calorimetry (DSC) was used to determine the bound water content in meat samples. The latent heat of melting (ΔHm) and bound water were found to be functions of moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 19 publications
9
67
0
1
Order By: Relevance
“…Similar findings were reported by Unal et al (2006) that polyionic properties enable phosphates to attach to protein molecules on positive sites, leading to increased protein solubility and enhanced water binding. Aktas et al (2003) demonstrated an increase in water-holding capacity, which was attributed to a rise in protein solubility and an increase in ions, as a result of salt marination.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Unal et al (2006) that polyionic properties enable phosphates to attach to protein molecules on positive sites, leading to increased protein solubility and enhanced water binding. Aktas et al (2003) demonstrated an increase in water-holding capacity, which was attributed to a rise in protein solubility and an increase in ions, as a result of salt marination.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent were dedicated to beef (Aktas, Aksu, & Kaya, 2003;Burke & Monahan, 2003;Desmond & Troy, 2001;Ke, Huang, Decker, & Hultin, 2009), turkey (Goli, Ricci, Bohuon, Marchesseau, & Collignan, 2014) and poultry meats (Yusop, O'Sullivan, Kerry, & Kerry, 2010). Other authors have considered alkaline marinating; this process increases meat pH from its initial post-mortem ultimate value but not necessarily above pH 7.…”
Section: Introductionmentioning
confidence: 97%
“…The other interesting observation in this work is that the tamarind juice plus salt and satay marinade treated meats showed similar effects in terms of weight gain for all the three types of muscles thus agrees with the previous investigation by Cheok (2009). The comparison of this marination using tamarind juice with other marination studies using numerous organic acids, such as acetic (Gault, 1985), citric (Aktaş et al, 2003), lactic acid (Aktaş et al, 2003), citrus juice (Burke and Monahan, 2003) and grapefruit juice (Serdaroğlu et al, 2006) on meat is probably difficult as all these workers marinated meat either for 24 hours or 72 hours at 4 C in their selected organic acid while for this work, a marinating time of 3 hours at 4C was chosen as recommended by Dompok (1999) and with the purpose of emulating the common household culinary preparation of marinating meat for one to two hours prior to cooking in Malaysia. Figure 3 shows the cooking loss of BR, BF and ST muscles in each marination treatments and the brine solution gave the lowest cooking loss (P < 0.01).…”
Section: Effect Of Muscle Types On Weight Gainmentioning
confidence: 99%
“…The meat samples were grilled in an oven (NN-J993, Panasonic, Japan) at 150 C for 8 minutes on a stainless steel tray, after which its weight was recorded as W 2 (g) following cooling to room temperature and removal of excessive moisture by gently dabbing the surface with paper towel (García-Segovia et al, 2007). The weight gain (Aktaş et al, 2003;Gravier et al, 2006;Serdaroğlu et al, 2007) and cooking loss (Baublits et al, 2006;García-Segovia et al, 2007;Obuz et al, 2003) at every marinating interval were calculated as follow: …”
Section: Weight Gain and Cooking Loss Calculationmentioning
confidence: 99%
See 1 more Smart Citation